Aron Gurwitsch e os primórdios da possibilidade de uma Gestalt fenomenológica - Soares, Brenda Cardoso (2024)
Our research points to Aron Gurwitsch as the first phenomenologist to use principles of Gestalt Theory in phenomenology, presenting how he introduces them into the description of the internal organization of his proposed structure of consciousness. By indicating a parallel between the transcendental reduction and the refutation of the constancy hypothesis, Gurwistch justifies the presence of Gestalt principles in the transcendental dimension. These principles are used by the philosopher to support his thematic phenomenology based on the theme and its contextual relationship with the thematic field, as objective structures guiding the flow of our states of consciousness. This leads to a renewal of attention that ceases to be subjectively directed and unfolds in a series of thematic modifications that demonstrate that there is no need for a pure and external subjectivity to acts of consciousness to direct, unify and identify them